Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1039/c5ra10658c
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of partial least squares and multivariate curve resolution for simultaneous spectrophotometric determination of pharmaceuticals in environmental samples

Abstract: 25 The potential of partial least squares regression (PLSR) and multivariate curve resolution 26 alternating least squares (MCR-ALS) is evaluated for simultaneous determination of 27 diclofenac (DCF), naproxen (NAP), mefenamic acid (MEF) and carbamazepine (CBZ) 28 as target analytes and gemfibrozil (GEM) as interference in synthetic and real 29 environmental samples. The analysis of first-order UV-Vis spectra is performed using 30 PLSR with different variable selection methods including variable importance in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 36 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…is study established a spectrophotometric method using MCR-ALS for simultaneous determination of imipramine, carbamazepine, chlorpromazine, haloperidol, and phenytoin in commercial formulations. An overview of analytical methods reported for the determination of CNS affecting drugs in pharmaceutical dosage forms revealed that all reported methods [6][7][8][9][10][11] either use or generate harmful solvents. Moreover, LODs of the proposed method were similar to or even better than those of the reported methods.…”
Section: Literature Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…is study established a spectrophotometric method using MCR-ALS for simultaneous determination of imipramine, carbamazepine, chlorpromazine, haloperidol, and phenytoin in commercial formulations. An overview of analytical methods reported for the determination of CNS affecting drugs in pharmaceutical dosage forms revealed that all reported methods [6][7][8][9][10][11] either use or generate harmful solvents. Moreover, LODs of the proposed method were similar to or even better than those of the reported methods.…”
Section: Literature Comparisonmentioning
confidence: 99%
“…Several methods have been developed for the analysis of these drugs, either individually or in combination. For example, partial least squares (PLS) and MCR-ALS were used for the simultaneous determination of carbamazepine along with diclofenac, naproxen, and other anti-inflammatory drugs [6]. HPLC-DAD was used for the analysis of carbamazepine and phenobarbital in human serum samples and was further evaluated by the MCR-ALS method [7].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to chromatographic methods that utilize sophisticated instruments and consume or generate large volumes of organic solvents, spectrophotometric methods are faster, more economical, and greener, making them fully functional alternatives. However, spectrophotometric techniques suffer from lack of selectivity especially in case of severe spectral overlap and matrix interferences, the selectivity of such techniques can be enhanced by using multivariate calibration models [8, 9]. The development of multivariate calibration methods such as multivariate curve resolution-alternating least squares (MCR-ALS) (based on signals mathematical resolution) enables the resolution and quantification of strongly overlapped spectra of multicomponent samples [10].…”
Section: Introductionmentioning
confidence: 99%
“…MCR-ALS has recently attracted attention in the analytical chemistry society and has been shown to provide enhanced resolution and improved quantitative determination of different analytes in samples of increasing complexity such as environmental matrices [11] and pharmaceutical and agricultural samples [10, 12]. The main advantage of using MCR-ALS is the possible recovery of the spectral information of target analytes and unknown interferences [9]. Different analytical methods have been developed for the individual assay of the OTC pain relievers and also for some of their combinations including HPLC (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…When one uses first order data (e. g., UV-Vis spectra) the appearance of overlapping spectra and matrix effects may reduce the accuracy and precision of the analysis. Multivariate calibration methods have been proposed to overcome fundamental mathematical challenges occurred during analysis of these types of data [12]. Among different multivariate calibration techniques, projection-based methods such as principal component regression (PCR) and partial least squares (PLS) have attracted attention in recent years and these methods have been used for determination of different analytes in various types of matrices [13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%